CASE BRIEF: LÓPEZ RIBALDA Y OTRAS V. ESPAÑA - Valenzuela Dávila, Alejandro (2020)
This article analyzes the sentence issued by the Grand Chamber of the European Court of Human Rights, on the case of “López Ribalda et al. Spain "in October 17, 2019. This text summarizes the most relevant aspects of the resolution, as well as the analysis on the merits of the Court's decision.